2019
DOI: 10.4149/bll_2018_140
|View full text |Cite
|
Sign up to set email alerts
|

Is elevated triglyceride high density lipoprotein cholesterol ratio a risk factor that causes acute coronary syndrome to appear earlier?

Abstract: BACKGROUND: The purpose of this study was to assess the relationship between the triglyceride/high density lipoprotein cholesterol ratio and the risk of acute myocardial infarction in young adults. PATIENTS AND METHODS: A total of 621 patients, who underwent coronary angiography (CAG) due to Myocardial Infarction (MI) at our hospital were included in this study. Demographic characteristics, risk factor profi le, laboratory test results, electrocardiographic and CAG fi ndings were assessed in the selected group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Recently, the TG/HDL-C ratio was also reported to be related to CHD. It has been demonstrated that the TG/HDL-C ratio may be an important predictor for an acute coronary syndrome in the young adult population and can even be used to prevent myocardial infarction in young adults [31]. In the present study, the TG/HDL-C ratio was also significantly higher in young nondiabetic patients with CHD when compared to those without CHD.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, the TG/HDL-C ratio was also reported to be related to CHD. It has been demonstrated that the TG/HDL-C ratio may be an important predictor for an acute coronary syndrome in the young adult population and can even be used to prevent myocardial infarction in young adults [31]. In the present study, the TG/HDL-C ratio was also significantly higher in young nondiabetic patients with CHD when compared to those without CHD.…”
Section: Discussionsupporting
confidence: 57%
“…26 In a study on the association between triglycerides/HDL and acute coronary syndrome, a number of scholars found that increased triglycerides/HDL were associated with the development of AMI in young adults. 27,28 Given the risk factors of young AMI patients, we recommend enhanced screening of patients with a family history of hyperlipidaemia, regular or enhanced follow-up, reasonable management of those at risk with a family history of hyperlipidaemia, and complementary early rehabilitation care interventions to modify risk factors in young patients with the disease. For patients with unhealthy lifestyles, we advise them to manage their lives by reducing the frequency of smoking and alcohol consumption and increasing their intake of vegetables and For patients with abnormal serological indicators, we advise patients to eat a light diet, reduce the intake of fried foods and animal offal, and increase physical activity when used.…”
Section: Discussionmentioning
confidence: 99%
“…In female patients, it has been shown that the TG / HDL-C ratio is independently associated with major cardiovascular events in patients presenting with revascularized STelevation myocardial infarction (10). It has been shown that the TG / HDL-C ratio may be an important predictor for acute coronary syndrome in the young adult population (19). In addition, after a successful revascularization for acute coronary syndrome, TG / HDL-C ratio was determined to be a risk factor for revascularization (20).…”
Section: Discussionmentioning
confidence: 99%